Use of Organic Compost for the Fertilization of Piatã and Paiaguás Grasses: Effects of Dose on Morphogenetic, Structural, Nutritional, and Productive Characteristics. Issue 3 (3rd July 2018) - Orrico Junior, Marco Antonio Previdelli; Silveira, Adriano Pereira da; Orrico, Ana Carolina Amorim; Schwingel, Alice Watte; Carnavali, Paulo Lópes; Alves, Daniel Chiari
ABSTRACT: The use of organic compost in pasture fertilization is a form of recycling nutrients contained in waste and reducing chemical fertilizer use. To perform pasture fertilization, however, grass responses to doses of organic composts must be known. Thus, the objective of this study was to find the best dose of laying hen organic compost to maximize the productive, morphogenetic, structural, and nutritional responses of Paiaguás and Piatã grasses. A completely randomized factorial (4 × 2) design was used, composed of organic compost doses (0, 400, 800, and 1, 200 kg equivalent N.ha −1 ) and two cultivars (Piatã and Paiaguás) of Urochloa brizantha grass with three replicates per treatment, assessed during four successive cuts. The parameters evaluated were dry matter yield (DM) of shoots and roots, leaf appearance rate (LAR), leaf elongation rate (LER), phyllochron, pseudoculm elongation rate (PER), final leaf length (FLL), number of green leaves (NGL), and senescence rate (SR). The nutritional value of the grasses was also assessed through contents of dry matter, organic matter, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber, cellulose, hemicellulose, lignin, and in vitro organic matter digestibility (IVOMD). DM yields of both shoot and root increased due to nitrogen increase and Paiaguás grass had the highest yields ( P < 0.01). The best organic compost doses ranged from 640 to 950 kg of equivalent N.ha −1 for most morphogenic and structural grass characteristics. The chemical composition of grasses was not influenced ( P > 0.05) by doses of organic compost. Levels of 8.05% CP, 67.10% NDF, and 65.14% IVOMD were observed for cultivar Paiaguás, while for cultivar Piatã these values were 7.58% CP, 70.32% NDF, and 63.38% IVOMD. It is concluded that high doses of an organic compost are required (in equivalent N) for cultivars to reach the highest growth rates and that Paiaguás grass has higher dry matter yield, higher growth rates, and better chemical composition when compared to Piatã grass in similar organic fertilization conditions.